Linguistic diversity, minority languages and minorities in the new EU constitutional treaty - Brezigar, Bojan (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The article brings an analysis of all the aspects of the EU Constitutional Treaty regarding languages and minorities. The anlysis is divided into four parts. The first part concerns constitutional languages of the EU, the rights of the EU citizens and obligations on the part of European institutions as to the use of these languages. The second part brings provisions on the prohibition of discrimination together with an analysis of the EU's competencies in the field of prevention and elimination of discrimination. Thethird part deals with the topic of cultural and linguistic diversity as a principle, which first appeared in the EU Charter on the basic rights; this principle is supposed to be one of the aims of the EU according to the Constitutional Treaty. The fourth part, finally, deals with the aspects which are specifically related to minorities and minority languages, and represent absolute novelty, regarding the previous European treaties. In each of the four parts the author points at the possible positive and negative effects.
Keywords: European Union; Evropska unija; narodne manjšine; jezikovne manjšine; ustave